A three-dimensional theory of law - Falcón y Tella, María José (Martinus Nijhoff Publishers, 2010)
What this book intends to do is to study three-dimensionalism (the distinction values-norms-facts) not in what could be called its historical dimension, but in its substantive aspect, as a ""form"" that, when applied to different legal themes